2017
DOI: 10.4049/jimmunol.1700373
|View full text |Cite
|
Sign up to set email alerts
|

A Consensus Definitive Classification of Scavenger Receptors and Their Roles in Health and Disease

Abstract: Scavenger receptors constitute a large family of proteins that are structurally diverse and participate in a wide range of biological functions. These receptors are expressed predominantly by myeloid cells and recognize a diverse variety of ligands including endogenous and modified host-derived molecules and microbial pathogens. There are currently eight classes of scavenger receptors, many of which have multiple names, leading to inconsistencies and confusion in the literature. To address this problem, a work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
204
0
23

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(227 citation statements)
references
References 168 publications
(179 reference statements)
0
204
0
23
Order By: Relevance
“…41 CD36 is involved in the recognition of a diverse array of pathological and physiological ligands, including members of a family of specific oxidized phospholipids, oxPC CD36 . 42 CD36 mediated the recognition of oxPC CD36 in oxidized LDL and subsequent binding and internalization of oxidized LDL by macrophages in the arterial wall contributes to atherogenesis in hyperlipidemic mice.…”
Section: Discussionmentioning
confidence: 99%
“…41 CD36 is involved in the recognition of a diverse array of pathological and physiological ligands, including members of a family of specific oxidized phospholipids, oxPC CD36 . 42 CD36 mediated the recognition of oxPC CD36 in oxidized LDL and subsequent binding and internalization of oxidized LDL by macrophages in the arterial wall contributes to atherogenesis in hyperlipidemic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Many phagocytosis receptors play dual roles, including both internalization and adhesion, and these two activities can activate each other [19,20]. Scavenger receptors often function by various mechanisms, including adhesion, phagocytosis, and signaling [51]. A previous study showed that CD36 is essential for LDL-induced macrophage spreading and actin polymerization [28].…”
Section: Discussionmentioning
confidence: 99%
“…γδ T cells) (Chaplin, 2010; Sonnenberg and Artis, 2015). These effector cells often use pattern recognition molecules such as Toll-like receptors (TLRs), NOD-like receptors (NLRs), and scavenger receptors to sense pathogens and danger signals that inititate innate immune responses (Chaplin, 2010; PrabhuDas et al, 2017). Innate immune cells can then release chemokines and cytokines that amplify the immune response by recruiting other immune cells and promoting inter-cellular signaling at the site of injury or infection and distal signaling via the circulatory system.…”
Section: Introductionmentioning
confidence: 99%
“…These molecules interact with receptors such as Toll-like receptors (TLRs) nucleotide-binding oligomerization domain (NOD) like receptors (NLRs) and scavenger receptors that serve as “danger” sensors and help initiate the inflammatory cascade (Jounai et al, 2012; Matzinger, 1994; PrabhuDas et al, 2017). TLR4, which recognizes lipopolysaccharides and multiple endogenous proteins such as high mobility group box 1 protein (HMGB1), heat shock proteins (HSPs), low-density lipoprotein, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation